2014
DOI: 10.1063/1.4896612
|View full text |Cite|
|
Sign up to set email alerts
|

Communication: Molecular-level insights into asymmetric triblock copolymers: Network and phase development

Abstract: Molecularly asymmetric triblock copolymers progressively grown from a parent diblock copolymer can be used to elucidate the phase and property transformation from diblock to network-forming triblock copolymer. In this study, we use several theoretical formalisms and simulation methods to examine the molecular-level characteristics accompanying this transformation, and show that reported macroscopic-level transitions correspond to the onset of an equilibrium network. Midblock conformational fractions and copoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Interfacial chain packing and curvature (and, hence, morphology) are largely dictated by f , whereas χN reveals that the onset of nanostructure formation at the order–disorder transition (ODT) is sensitive to temperature (since χ is frequently expressed as α + β/ T , where T denotes absolute temperature) and molecular weight. A strategy developed to alter the phase behavior of bicomponent block copolymers relies on changing the molecular architecture by either (i) increasing the number of blocks/molecule from diblock to triblock to higher order multiblock or (ii) switching from linear to nonlinear motifs . In the first case, a systematic increase in the size of a second endblock in the transition from AB diblock to ABA triblock copolymer generates asymmetric A 1 BA 2 copolymers that have not only elucidated unexpected phase behavior and the mechanism by which midblock bridging proceeds but also revealed that coexisting morphologies can arise in the limit of super strong segregation .…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial chain packing and curvature (and, hence, morphology) are largely dictated by f , whereas χN reveals that the onset of nanostructure formation at the order–disorder transition (ODT) is sensitive to temperature (since χ is frequently expressed as α + β/ T , where T denotes absolute temperature) and molecular weight. A strategy developed to alter the phase behavior of bicomponent block copolymers relies on changing the molecular architecture by either (i) increasing the number of blocks/molecule from diblock to triblock to higher order multiblock or (ii) switching from linear to nonlinear motifs . In the first case, a systematic increase in the size of a second endblock in the transition from AB diblock to ABA triblock copolymer generates asymmetric A 1 BA 2 copolymers that have not only elucidated unexpected phase behavior and the mechanism by which midblock bridging proceeds but also revealed that coexisting morphologies can arise in the limit of super strong segregation .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the thermodynamic incompatibility between these sequences, the copolymers typically self‐assemble and form soft nanoscale morphologies ranging from classical nanostructures (e.g., spheres, cylinders, and lamellae) to more spatially complex ones (e.g., gyroid, Fddd , and truncated octahedra). Bicomponent triblock (as well as higher‐order multiblock) copolymers consisting of glassy endblocks and a rubbery midblock are of noteworthy interest as thermoplastic elastomers (TPEs) in that they not only microphase‐separate to form the same morphologies as their diblock analogs, but also generate a molecular network wherein rubbery midblocks connect neighboring glassy microdomains (which act as physical crosslinks). Unlike their chemically crosslinked counterparts, TPEs can thus be recycled and reused after their application lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…This transition leads to formation of a plethora of different nanostructures, such as ordered layers, hexagonally arranged cylinder, cubically ordered spheres or a double gyroid phase. Previous studies [17][18][19][20][21][22][23] of molecularly asymmetric A1BA2 triblock copolymers synthesized from a parent diblock copolymer so that N A1 is significantly smaller than N A2 (where N A1 and N A2 denote the number of repeat units in the A1 and A2 blocks, respectively) have helped to elucidate the molecular and property changes accompanying the transformation from an AB diblock to a molecularly symmetric ABA triblock copolymer (with N A1 = N A2 ). Recent Monte Carlo (MC) simulations of moderately segregated copolymers have yielded results that quantitatively agree with unexpected experimental findings, most notably a pronounced minimum in the order-disorder transition temperature as N A2 is progressively increased.…”
Section: Introductionmentioning
confidence: 99%